2015
DOI: 10.1242/dev.128819
|View full text |Cite
|
Sign up to set email alerts
|

A new Xist allele driven by a constitutively active promoter is dominated by Xist locus environment and exhibits the parent-of-origin effects

Abstract: The dosage difference of X-linked genes between the sexes in mammals is compensated for by genetic inactivation of one of the X chromosomes in XX females. A noncoding RNA transcribed from the Xist gene at the onset of X chromosome inactivation coats the X chromosome in cis and induces chromosome-wide heterochromatinization. Here, we report a new Xist allele (Xist CAG ) driven by a CAG promoter, which is known to be constitutively active in many types of cells. The paternal transmission of Xist CAG resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…This suggests that a mechanism for the random choice of monoallelic upregulation is still effective on either the wild-type or Xist CAGΔ5′ allele despite the fact that Xist CAGΔ5′ is driven by the CAG promoter. This appears consistent with our recent finding that, in undifferentiated ESCs, the CAG promoter driving the Xist CAG allele does not efficiently promote transcription but rather behaves in a manner similar to the endogenous Xist promoter, causing only a basal level of transcription (Amakawa et al, 2015). We anticipate that, given the constitutively active nature of the CAG promoter in many differentiated cells, monoallelic upregulation of the wild-type Xist allele at the onset of XCI should be followed by upregulation of Xist An X chromosome acquires a series of epigenetic modifications following the accumulation of Xist RNA and forms a silencing compartment, into which X-linked genes that are to be silenced relocate (Escamilla-Del-Arenal et al, 2011;Patrat et al, 2009).…”
Section: Discussion the A-repeat Is Essential For XCI During Embryogesupporting
confidence: 93%
See 4 more Smart Citations
“…This suggests that a mechanism for the random choice of monoallelic upregulation is still effective on either the wild-type or Xist CAGΔ5′ allele despite the fact that Xist CAGΔ5′ is driven by the CAG promoter. This appears consistent with our recent finding that, in undifferentiated ESCs, the CAG promoter driving the Xist CAG allele does not efficiently promote transcription but rather behaves in a manner similar to the endogenous Xist promoter, causing only a basal level of transcription (Amakawa et al, 2015). We anticipate that, given the constitutively active nature of the CAG promoter in many differentiated cells, monoallelic upregulation of the wild-type Xist allele at the onset of XCI should be followed by upregulation of Xist An X chromosome acquires a series of epigenetic modifications following the accumulation of Xist RNA and forms a silencing compartment, into which X-linked genes that are to be silenced relocate (Escamilla-Del-Arenal et al, 2011;Patrat et al, 2009).…”
Section: Discussion the A-repeat Is Essential For XCI During Embryogesupporting
confidence: 93%
“…Since our previous study revealed that a simple deletion of the A-repeat abolished Xist upregulation during embryonic development (Hoki et al, 2009), we decided instead to express Xist RNA lacking the A-repeat using a CAG promoter, using the same approach as we used previously to create the Xist CAG allele (Amakawa et al, 2015). The 5′ region of Xist spanning from its endogenous promoter to the XhoI site 0.9 kb downstream of the major transcription start site in exon 1 was replaced with a fragment containing the CAG promoter and a floxed selection marker by gene targeting to generate the Xist CAGΔ5′-2L allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations